2013
DOI: 10.1186/1471-2458-13-322
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce neonatal mortality from neonatal tetanus in low and middle income countries - a systematic review

Abstract: BackgroundIn 1988, WHO estimated around 787,000 newborns deaths due to neonatal tetanus. Despite few success stories majority of the Low and Middle Income Countries (LMICs) are still struggling to reduce neonatal mortality due to neonatal tetanus. We conducted a systematic review to understand the interventions that have had a substantial effect on reducing neonatal mortality rate due to neonatal tetanus in LMICs and come up with feasible recommendations for decreasing neonatal tetanus in the Pakistani setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 15 publications
2
52
1
Order By: Relevance
“…4 The enormity of the danger posed by the poor obstetric care services across the continent is demonstrated by the finding in a study conducted at the Kilifi County Hospital, Kenya, that reported that 98% of the neonatal tetanus admissions at the hospital from 1999 to 2013 were home deliveries. 5 While evidence from studies has shown that immunization of pregnant women or women of child bearing age with two or more doses of tetanus vaccine (TT2+) protects the mother and the newborn baby from tetanus (with 94% reduction in mortality from neonatal tetanus), and at least 80% TT2+ coverage is needed to achieve MNT elimination, 6,7 data from the Nigeria Demographic and Health Survey (NDHS) 2013 showed wide variation and predominantly low TT2+ coverage rates across the country, ranging from 27.1% in the North-West geopolitical zone of the country (the study area) to 82.0% in the South-East zone; and with a national TT2+ coverage rate of 48%. 4 Similar to the situation in Nigeria, studies conducted in other sub-Saharan African countries including Ethiopia, 8 Kenya, 9 and Benin Republic, 10 also established a direct association between health facility utilization by pregnant women (particularly antenatal clinic attendance) and acceptance of TTCV by them, as the ANC visits avail the healthcare providers the opportunity to educate them on the benefits of TT immunization and its schedule.…”
Section: Introductionmentioning
confidence: 99%
“…4 The enormity of the danger posed by the poor obstetric care services across the continent is demonstrated by the finding in a study conducted at the Kilifi County Hospital, Kenya, that reported that 98% of the neonatal tetanus admissions at the hospital from 1999 to 2013 were home deliveries. 5 While evidence from studies has shown that immunization of pregnant women or women of child bearing age with two or more doses of tetanus vaccine (TT2+) protects the mother and the newborn baby from tetanus (with 94% reduction in mortality from neonatal tetanus), and at least 80% TT2+ coverage is needed to achieve MNT elimination, 6,7 data from the Nigeria Demographic and Health Survey (NDHS) 2013 showed wide variation and predominantly low TT2+ coverage rates across the country, ranging from 27.1% in the North-West geopolitical zone of the country (the study area) to 82.0% in the South-East zone; and with a national TT2+ coverage rate of 48%. 4 Similar to the situation in Nigeria, studies conducted in other sub-Saharan African countries including Ethiopia, 8 Kenya, 9 and Benin Republic, 10 also established a direct association between health facility utilization by pregnant women (particularly antenatal clinic attendance) and acceptance of TTCV by them, as the ANC visits avail the healthcare providers the opportunity to educate them on the benefits of TT immunization and its schedule.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 In some resourcepoor settings of the world, unsterile deliveries and poor post-natal hygiene compound the risk of neonatal tetanus. [12][13][14][15] The cultural diversity of childbirth practices and cord management, untrained birth attendants, uneducated parents, poor antenatal care and lack of immunization against tetanus have also been associated with the disease. 4,5,16,17 Furthermore, seasonality, geographical location, climate, prevalence of C. tetani and a rural agricultural population are also related to the incidence of neonatal tetanus.…”
mentioning
confidence: 99%
“…Financial difficulty in another emerged as the major issue among women who did not fulfil the minimum requirements of four antenatal care services or two postnatal care services within the first month after delivery [10], [11]. This was related to the cost of health services, transportation costs, or both.…”
Section: (B) Financialmentioning
confidence: 99%